2023
DOI: 10.9734/ijecc/2023/v13i61792
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Boron on Growth and Yield of Sweet Corn (Zea mays L. Saccharata) Varieties

Abstract: At the Department of Agronomy's Crop Research Farm, SHUATS, Prayagraj, a field experiment was carried out in the month of Zaid 2022. (U.P). The soil in the experimental plot had a sandy loam texture, a pH of 7.1 that was almost neutral, a low level of organic carbon (0.36%), and low availability of the nutrients N, P, K  (171.48 kg/ha, 15.2 kg/ha, and 232.5 kg/ha, respectively). Ten treatments, each replicated three times, were used in the experiment, which was set up using a randomised block design over the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Additionally, Sai Ram and Dawson reported that application of 15 kg Zinc with B 1.5% as foliar spray recorded highest plant height [10]. Lastly, Kumar et al [9] found that treatment T9-Misthi + 0.3% B foliar application was recorded significantly higher plant height. These findings demonstrate the positive effect of B application on the growth and yield of maize plants, including plant height.…”
Section: Mm) On Root Mass Showing: Grams Fresh Weight Of Root (A) Num...mentioning
confidence: 95%
See 4 more Smart Citations
“…Additionally, Sai Ram and Dawson reported that application of 15 kg Zinc with B 1.5% as foliar spray recorded highest plant height [10]. Lastly, Kumar et al [9] found that treatment T9-Misthi + 0.3% B foliar application was recorded significantly higher plant height. These findings demonstrate the positive effect of B application on the growth and yield of maize plants, including plant height.…”
Section: Mm) On Root Mass Showing: Grams Fresh Weight Of Root (A) Num...mentioning
confidence: 95%
“…Another study found that treatment with Misthi variety and 0.3% B foliar application resulted in the highest cob length (18.5 cm) and grain yield (9.5 t/ha) [37]. Additionally, the application of 15 kg zinc with 1.5% B as a foliar spray recorded the highest number of grains per cob (523.93) and grain yield (6.33 t/ha) [9]. These findings suggest that B application, in combination with other nutrients, can enhance maize cob size and yield.…”
Section: Effect Boron On Maize Yieldmentioning
confidence: 97%
See 3 more Smart Citations